2021
DOI: 10.1039/d0nj05475e
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide–porphyrin composite nanostructure included electrochemical sensor for catechol detection

Abstract: A novel composite nanostructure (GO–Por) has been prepared via ultrasonication and exhibited enhanced electrocatalytic activity towards catechol oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The FTIR spectrum of pure FePor (Figure S2a) showed characteristic absorption peaks at 1698, 753, and 711 cm –1 , which could be assigned to the porphyrin skeletal vibrations. , The absorption peaks at 1412 and 1087 cm –1 were attributed to the CN stretching vibration of the pyrrole ring and C–N stretching vibration of the porphyrin ring, respectively. , Another peak at 1299 cm –1 could be assigned to the characteristic peak of −OH vibration. Moreover, the peaks at 968 and 846 cm –1 were related to the C–N bending vibration and macrocycle ring out-of-plane deformation . Comparing the FTIR spectra of FePor and FePor-PQ electrodes with pure FePor, it can be observed that the composite electrodes still showed the characteristic peaks belonging to pure FePor, revealing that FePor has been successfully introduced into the composite electrodes.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The FTIR spectrum of pure FePor (Figure S2a) showed characteristic absorption peaks at 1698, 753, and 711 cm –1 , which could be assigned to the porphyrin skeletal vibrations. , The absorption peaks at 1412 and 1087 cm –1 were attributed to the CN stretching vibration of the pyrrole ring and C–N stretching vibration of the porphyrin ring, respectively. , Another peak at 1299 cm –1 could be assigned to the characteristic peak of −OH vibration. Moreover, the peaks at 968 and 846 cm –1 were related to the C–N bending vibration and macrocycle ring out-of-plane deformation . Comparing the FTIR spectra of FePor and FePor-PQ electrodes with pure FePor, it can be observed that the composite electrodes still showed the characteristic peaks belonging to pure FePor, revealing that FePor has been successfully introduced into the composite electrodes.…”
Section: Resultsmentioning
confidence: 92%
“…Moreover, the peaks at 968 and 846 cm −1 were related to the C−N bending vibration and macrocycle ring out-of-plane deformation. 34 Comparing the FTIR spectra of FePor and FePor-PQ electrodes with pure FePor, it can be observed that the composite electrodes still showed the characteristic peaks belonging to pure FePor, revealing that FePor has been successfully introduced into the composite electrodes.…”
Section: Resultsmentioning
confidence: 98%
“…The immunoelectrode is found to be specific, reproducible, and regenerable up to 4 cycles, and it has a shelf life of up to 6 weeks. The sensor has an electroactive surface area of 0.55 cm 2 and a HET rate of À4.05 Â 10 À3 cm s À1 . Its excellent electrochemical performance towards the detection of NSE can be attributed to: (1) the cumulative effect of MoS 2 and CS, which imparts stability and biocompatibility to the matrix; (2) the introduction of functional groups that lead to covalent attachment between the antibodies and the matrix without the use of any harsh chemicals; and (3) the electroactive surface area, which is 55% of the geometric area.…”
Section: Discussionmentioning
confidence: 99%
“…Electrochemical biosensors have gained momentum in the development of point-of-care devices owing to their ease of miniaturization, the requirement of small sample volumes, their rapid response, and low requirement for power. 1,2 They use electron mediators to translate the events of analyte binding into a detectable electrical signal. The preparation of an electrochemical biosensor requires the fabrication of a suitable immobilization matrix that can hold the bio-recognition elements efficiently and effectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation